Community participation in healthy cities in China: an analysis of text data collected through a national crowdsourcing contest. (December 2017) - Wu, Dan; Wei, Shufang; Zhang, Yu; Liu, Xiayan; Stein, Gabi; Liu, Chuncheng; Cong, Na; Best, Lucy L; Pan, Stephen; Tang, Weiming; Fu, Hongyun; Ong, Jason; et al.
Abstract: Background: Community participation is fundamental to defining and developing healthy cities. This study examined public perceptions of healthy cities in China. Methods: A steering committee organised a crowdsourcing contest during 8 weeks from January to February, 2017. Crowdsourcing contests invite a large group of individuals to complete a task. The committee distributed an open call for entries to the public through social media soliciting descriptions of healthy cities and strategies for creating healthy cities. Participants submitted texts, images, and videos online. We extracted the text entries and analysed the data using a thematic approach. Three individuals independently coded the data. All contest data were de-identified and exempted from ethical review by the Institutional Review Committee at the University of North Carolina at Chapel Hill. Findings: We received 251 text descriptions and 231 were eligible and coded. Thematic analysis revealed components of what a healthy city ought to include and strategies for creating healthy cities. The public noted that a healthy city ought to provide sustainable local environments, elements essential for livelihood (food and income security, clean water), physical infrastructure, a fair education system, just laws and judicial system, and a cohesive society. Strategies for creating healthy cities included public education, community engagement, urban planning, environmental improvements, and policies. Some remarked that urban floods were common and recommended sponge cities using water-permeable materials to capture, control, and recycle rainwater to mitigate the impact of floods. A few participants suggested that urban cities had limited space and vertical farming could take advantage of spare space in buildings and natural resources for planting. Another participant described an online waste recycling system in which people gain credits for recycling waste and use the credits to purchase other products. Interpretation: Text descriptions from a crowdsourcing contest helped to understand public perceptions of healthy cities in China. Community participation might help healthy city planning to become more people-centred. Funding: Tsinghua University and SESH Global. The listed grant funders played no role in any step of this study.